Functional Gene Module–Based Identification of Phillyrin as an Anticardiac Fibrosis Agent - Wang, Lei; Zhang, Wuxia; Lu, Ziwen; Wang, Baofu; Li, Yang; Yang, Jingjing; Li, Peng; Zhao, Mingjing (Frontiers in Pharmacology, 2020)
The cardiac fibrosis (CF) greatly influences the therapeutic effects for heart diseases and remains an urgent challenge in clinical therapy. Till now, there are few methods to effectively find potential anti-CF drugs. In this study, we aimed to construct a gene functional module to represent the core pathological process for CF and then used this module to screen antifibrotic agents that have the abilities to decrease the expression of the module. Firstly, Three CF marker genes POSTN, DDR2 and PDGFRA were selected to identify their top co-expressed genes in the genome-based transcriptional profiles of human hearts, both the marker genes and the co-expressed genes composed the CF related gene functional module. Secondly, the correlation of the module with CF process was measured in a collection of gene expression profiles of heart diseases to evaluate the participation of functional module within heart diseases. Thirdly, the anti-CF effects of phillyrin was predicted by enrichment analysis of the module in the phillyrin-induced transcriptional profile. Finally, the myocardial infarction (MI) animal model was utilized to experimentally validate the cardioprotective and anti-CF effects of phillyrin.